Flexural behavior of 3D para-aramid/phenolic/nano (MWCNT) composites. Issue 13 (14th February 2018) - Bilisik, K.; Erdogan, G.; Sapancı, E.
Abstract : The bending properties of four types of nanostitched and nanoprepreg three dimensional (3D) para -aramid/phenolic composite were studied. Stitched or stitched/nano p -aramid/phenolic composites could be considered as damage tolerant materials. Abstract : In this work, the flexure properties of nanostitched and nanoprepreg three dimensional (3D) para -aramid/phenolic composites were studied. Four types of composite were developed. They were called stitched/nano, stitched, base/nano and base. The flexure strength and modulus of the stitched/nano composites were slightly improved compared to those of the base composites due to the addition of the stitching yarn and multiwall carbon nanotubes (MWCNTs). The flexure failure of the base and base/nano structures was matrix peeling and large delaminated areas, whereas the stitched and stitched/nano composites had warp deformation and no visible matrix/fiber damage. In addition, the delaminated areas were severely restricted. The results showed that introducing the stitching fiber and multiwall carbon nanotubes in the base structure improved its out-of-plane failure properties as a form of restricted delamination and they acted as delamination barriers around the regions. Therefore, stitched/nano p -aramid/phenolic composites could be considered as damage tolerant materials.